Examining a successful high-performance triathlon environment from the coaching team perspective - Andronikos, G.; Westbury, T.; Souglis, A.; Travlos, A.; Martindale, R. J. (International Sport Coaching Journal, 2026)
This research aims to investigate an environment designed by a head coach with a track record of both highly successful talent development and world-class performance outcomes in the sport of triathlon. A qualitative approach involving semistructured interviews with the head coach, the psychologist, and the nutritionist was used. Key considerations regarding the selection of athletes were discussed, providing evidence for the key role of psychology and prolonged trials that allowed thorough understanding of the athlete, and insight into development capacity, as well as their contribution to the wider squad. In addition, a coaching team was embedded utilizing a multidisciplinary approach, and significant others were actively incorporated in the development process. Furthermore, the complexities of managing long-term development were highlighted, and the use of challenge as a mechanism of development was evident.